Achieving all the time, everywhere access in next-generation mobile networks. - Cinque, Marcello
The anytime, anywhere access view of nomadic computing is evolving towards all the time, everywhere views of pervasive computing. The all the time access requires mobile devices to be always connected, even if connectivity may be compromised due to Access Point overload and to transient signal degradations. The everywhere access requires mobile devices to use heterogeneous Access Points (ranging from Bluetooth and 802.11 to 2.5G and 3G cellulars), leading to high variability of the connection status. A mobility management solution that leverages connection availability, while enabling applications to be aware of the connection status, is thus needed. This paper proposes a Last Second Soft Handoff scheme that leverages the availability of connection. The proposed scheme has been integrated in a mobility management architecture, which provides connection awareness via an API, named NCSOCKS. Implementation issues are discussed and experimental results are provided.
Keywords: Computer Systems Organization; Computer communication networks; Network architecture and design; Wireless communication; Network protocols; Routing protocols; Applications (SMTP, FTP, etc.).; Local and wide area networks; Access schemes; Algorithms; Performance